Exercise Intervention Improves Clinical Outcomes, but the “Time of Session” is Crucial for Better Quality of Life in Breast Cancer Survivors: A Systematic Review and Meta-Analysis - Hong, Feng (Cancers (Basel), 2019)
This study examined the effects of exercise intervention on the quality of life (QoL), social functioning (SF), and physical functioning (PF) of breast cancer survivors, and identified the responsible and optimal exercise characteristics for amelioration of outcomes. Randomized controlled trials (RCTs) that adopted exercise intervention and measured the QoL, SF, and PF of breast cancer patients were included. We used meta-analysis to calculate the pooled effect, and meta-regression to identify the responsible exercise characteristics (type, frequency, duration, and time). Subgroup analysis assessed the optimal “time of session” for an improved QoL. The Cochrane risk-of-bias tool was used to determine the quality of studies. In the systematic review, we included 26 RCTs with a total of 1892 breast cancer patients, whilst 18 trials were considered for meta-analysis (exercise = 602; control = 603). The pooled effect showed that exercise intervention substantially improved the QoL (standardized mean difference (SMD) = 0.35; I(2) = 61%; 95% confidence internal (CI): 0.15–0.54; p = 0.0004), SF (SMD = 0.20; I(2) = 16%; 95% CI:0.08–0.32; p = 0.001), and PF (SMD = 0.32; I(2) = 32%; 95% CI:0.20–0.44; p < 0.00001). Meta-regression analysis showed that improved QoL was associated (p = 0.041) with the “time of session”. More specifically, sessions conducted for medium-time (>45 to ≤60 min; p = 0.03) and longer-time (>60 to 90 min; p = 0.005) considerably improved the QoL, whilst shorter-time (≤45 min; p = 0.15) did not. To summarize, exercise interventions improved the QoL, SF, and PF of breast cancer survivors, where the “time of session” appeared to be crucial for an effective improvement in the QoL.